Penerapan E-Learning dalam Lembaga Pendidikan Islam - Nur Habibuddin; Selvi Dewi Rahayu; Umi Kalsum; Fitriah Amina; Siti Nur Patimah; Juliana (Jurnal Pelita Manajemen Pendidikan, 2024)
The integration of Information and Communication Technology (ICT) in education, exemplified by the widespread adoption of e-learning, presents both opportunities and challenges, especially within Islamic educational institutions. This study aims to comprehensively examine the application of e-learning in Islamic educational institutions, exploring the philosophical foundations, opportunities, challenges, and implementation strategies. By employing a qualitative approach with case study methods, data was collected through in-depth interviews, participatory observation, and document analysis, providing a holistic and contextual perspective. The analysis revealed that while e-learning offers significant benefits such as increased flexibility, accessibility, and personalized learning, it also faces challenges like technological infrastructure issues, human resource readiness, resistance to change, and data security concerns. Specifically, in the context of Islamic education, concerns about the potential negative impacts of technology on Islamic values were identified. However, the study suggests that with a well-conceptualized framework integrating philosophical, pedagogical, and technological aspects, e-learning can enhance the quality of education and reinforce Islamic values. The findings also provide insights for policymakers and stakeholders in designing, implementing, and evaluating e-learning programs that align with Islamic educational principles. This research contributes to the ongoing development of e-learning practices in Islamic education and offers a foundation for future studies in this domain.